2019
DOI: 10.15414/afz.2019.22.01.21-25
|View full text |Cite
|
Sign up to set email alerts
|

Differences in soil properties and crop yields after application of biochar blended with farmyard manure in sandy and loamy soils

Abstract: In recent years, the importance of biochar application in world´s soils have increased tendency mainly due to its opposite effects. Therefore, the effort of many companies is based on the development of soil amendment which together improve properties and crop productivity in lot of soils. In this short study, we have verified the effectiveness of biochar blended with farmyard manure named Effeco on soil properties and crop yields in different textural soils (1. sandy soil in Dolná Streda and 2. loamy soil in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Various studies have shown that biochar has the potential to influence the soil water content, the available water capacity of the soil, the water holding capacity of the soil and field capacity (Busscher et al 2010;Novak et al 2012;Abel et al 2013 tion of biochar substrates and biochar substrates in combination with manure (OF) in comparison to respective controls (Table 2). Our findings are in the agreement with results of several authors (El-nagar et al 2019;Šimanský et al 2019b) who pointed to a more significant effect of biochar on water content increase of sandy soils. Tables 1 and 2 also show the results on the content of dry-sieved macro-aggregates (Dsa ma ) and micro-aggregates (Dsa mi ), as well as their ratios, and how they were affected by the application of different biochar substrates and biochar substrates combined with other fertilisers in texturally different soils.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Various studies have shown that biochar has the potential to influence the soil water content, the available water capacity of the soil, the water holding capacity of the soil and field capacity (Busscher et al 2010;Novak et al 2012;Abel et al 2013 tion of biochar substrates and biochar substrates in combination with manure (OF) in comparison to respective controls (Table 2). Our findings are in the agreement with results of several authors (El-nagar et al 2019;Šimanský et al 2019b) who pointed to a more significant effect of biochar on water content increase of sandy soils. Tables 1 and 2 also show the results on the content of dry-sieved macro-aggregates (Dsa ma ) and micro-aggregates (Dsa mi ), as well as their ratios, and how they were affected by the application of different biochar substrates and biochar substrates combined with other fertilisers in texturally different soils.…”
Section: Resultssupporting
confidence: 94%
“…a higher level of compaction was observed on arable soils, especially in fine-textured soil such as Fluvisols, Chernozems, stagnosols, and Cambisols (kobza et al 2017). Supplying soil with organic matter is the most effective measure for improving the physical properties of soils; the positive effect of this procedure has been confirmed in various studies (šimanský et al 2008;Rao et al 2017). For this reason, the issue of organic matter supply to soils requires special attention not only within the Eu or slovakia but worldwide.…”
mentioning
confidence: 88%
“…The lower biochar application dose (10 t ha −1 ) had no effect on the improvement of the soil structure. Biochar can improve the physical condition of the soil [37,60,61] through the supplied organic matter [62]. The surface of biochar particles after oxidation may contain the hydroxyl and carboxyl groups that are able to associate with the mineral and other organic soil particles to form soil aggregates [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate several benefits of nutrient-rich biochar pellets, including improvements in crop yield. For example, biochar pellets increased the yields of rice [9], tomato [13] and sunflower grain and peppers fruit [14]. Such an increase was associated with improved nutrient availability and soil health and quality.…”
Section: Discussionmentioning
confidence: 99%